Akt-Dependent Glycolysis-Driven Lipogenesis Supports Proliferation and Survival of Human Pulmonary Arterial Smooth Muscle Cells in Pulmonary Hypertension - Jiang, Lifeng; Goncharov, Dmitry A.; Shen, Yuanjun; Lin, Derek; Chang, Baojun; Pena, Andressa; DeLisser, Horace; Goncharova, Elena A.; Kudryashova, Tatiana V. (Frontiers in Medicine, 2022)
Hyper-proliferation of pulmonary arterial vascular smooth muscle cells (PAVSMC) is an important pathological component of pulmonary vascular remodeling in pulmonary arterial hypertension (PAH). Lipogenesis is linked to numerous proliferative diseases, but its role in PAVSMC proliferation in PAH remains to be elucidated. We found that early-passage human PAH PAVSMC had significant up-regulation of key fatty acids synthesis enzymes ATP-citrate lyase (ACLY), acetyl-CoA carboxylase (ACC), and fatty acid synthase (FASN), and increased unstimulated proliferation compared to control human PAVSMC. Treatment with an allosteric ACC inhibitor 5-tetradecyloxy-2-furoic acid (TOFA) significantly decreased proliferation and induced apoptosis of human PAH PAVSMC. Intracellular lipid content and proliferation of PAH PAVSMC were not reduced by incubation in lipid-depleted media but suppressed by a non-metabolizable analog of glucose 2-Deoxy-D-glucose (2-DG) and partially restored by addition of pyruvate. Protein kinase Akt was upregulated in human PAH PAVSMC in a sirtuin 7 (SIRT7)- and c-Jun N-terminal kinase (JNK)-dependent manner. Pharmacological inhibition of Akt down-regulated ACLY and ACC, significantly reduced intracellular lipid content, inhibited proliferation and induced apoptosis of human PAH PAVSMC. Taken together, these data demonstrate that human PAH PAVSMC have up-regulated lipogenesis, which is supported in an Akt- and glycolysis-dependent manner and is required for increased proliferation and survival. Our data suggest that there is a mechanistic link between glycolysis, lipogenesis, and the proliferation of human PAH PAVSMC and call for further studies to determine the potential attractiveness of a SIRT7/JNK-Akt-lipogenesis axis as a target pathway to inhibit PAVSMC hyper-proliferation in PAH.